Glucosylceramide modulates membrane traffic along the endocytic pathway. - Sillence, D; Puri, V; Marks, D; Butters, T; Dwek, R; Pagano, R; Platt, F (2002)
Glycosphingolipids are endocytosed and targeted to the Golgi apparatus, but are mistargeted to lysosomes in numerous sphingolipidoses. Substrate reduction therapy utilizes imino sugars to inhibit glucosylceramide synthase and potentially abrogate the effects of storage. Gaucher disease is a hereditary deficiency in glucocerebrosidase leading to glucosylceramide accumulation; however, Gaucher fibroblasts exhibited normal Golgi transport of lactosylceramide. To better understand the effects of glycosphingolipid accumulation on intracellular trafficking and the use of imino sugar inhibitors, we studied sphingolipid endocytosis in fibroblast and macrophage models for Gaucher disease. Treatment of fibroblasts or RAW macrophages with conduritol B epoxide, an inhibitor of lysosomal glucocerebrosidase, resulted in a change in the endocytic targeting of lactosylceramide from the Golgi to the lysosomes. Co-treatment of macrophages with conduritol B-epoxide and 12-25 microM N-butyldeoxygalactonojirimycin, an inhibitor of glycosphingolipid biosynthesis, prevented the mistargeting of lactosylceramide to the lysosomes and restored trafficking to the Golgi. Surprisingly, higher doses (>25 microM) of NB-DGJ induced targeting of lactosylceramide to the lysosomes, even in the absence of conduritol B-epoxide. These data demonstrate that both increases and decreases in glucosylceramide levels can dramatically alter the endocytic targeting of lactosylceramide and suggest a role for glucosylceramide in regulation of membrane transport.